The Role of The Political Party Court In Resolving Internal Political Party Disputes Based on The Political Parties Act - Cut Putri Nadia; Zainal Abidin; M. Jafar (International Journal of Law and Society, 2026)
Political parties often face internal conflicts known as internal party disputes. The resolution of internal political party disputes through a Party Court, as regulated in Law No. 2 of 2011 on Amendments to Law No. 2 of 2008 on Political Parties, in Article 32 paragraph (2), states: “The resolution of internal political party disputes as referred to in paragraph (1) shall be conducted by a Political Party Court or other body established by the political party,” which still leaves issues of legal ambiguity and uncertainty regarding the status and authority of the Political Party Court in resolving internal political party disputes under the Political Parties Law, as well as the role and authority of the District Court as a form of further legal recourse in resolving such disputes. This study aims to analyze and explain the position of the Political Party Court institution within a political party in resolving internal political party disputes, the authority of the Political Party Court to resolve internal political party disputes in providing legal certainty, and the authority of the District Court in resolving internal political party disputes. This study employs a normative legal method using a statutory approach, a conceptual approach, a case-based approach, and a comparative approach. The results indicate that the resolution of internal political party disputes through the Political Party Court and District Courts has not been effective in ensuring legal certainty. The Party Court remains weak in terms of independence, procedures, and the enforceability of its decisions, while the authority of the District Court is limited and tends to be formalistic. Consequently, uncertainty arises in dispute resolution, necessitating the strengthening of regulations and the establishment of a more integrated dispute resolution mechanism.